ANALISIS PEMODELAN PERMUKAAN TOPOGRAFI BERBASIS AUGMENTED REALITY UNTUK VISUALISASI KONTUR DAN HIDROLOGI - Miftahul Riski; Agung Budi Cahyono (Universitas Pendidikan Indonesia (UPI), 2021)
Information Technology in the delivery of information has developed rapidly. Augmented Reality (AR) is a 3D visual imaging technology. Topography in a broad sense is defined as the height of a place calculated from sea level so that the height of the land can be known. In Indonesia, the application of AR technology is only limited to displaying the results of visual forms in games. But the technology is still considered new to the world of education. In this study, we will analyze the form of visual modeling from AR as a media related to the visualization of topographical forms. By making installations related to tools in the form of a sandbox and an AR integration system that is used as a medium for topographic modeling. The analysis was carried out on 5 topographic models. The results obtained in the topographic modeling are the results obtained through the printed DEMNAS data modeling and then made a visual form in the AR sandbox tool. With the RMSe results obtained, it will affect the precision modeling results. From the comparison of contour line modeling results, there is a difference in the visualization form of the mound. The results of the hydrological modeling made a basin shape. By calling the command for the visual form of the water, a hydrological modeling model is obtained.Keywords: Augmented reality, Countour, DEMNAS, Education, Modelling, Topography,